Can walking capacity predict respiratory functions of people with Parkinson’s disease? - Matos, Lucas Meireles; Oliveira, Francisca Maria de Araujo; Rocha, Rodrigo Santiago Barbosa; Pimentel, Aline da Silva; Neves, Laura Maria Tomazi; Crisp, Alex Harley; Peyré-Tartaruga, Leonardo Alexandre; Correale, Luca; Coertjens, Marcelo; Passos-Monteiro, Elren (Frontiers in Neurology, 2025)
IntroductionPeople with Parkinson’s Disease (PwPD) and an impaired respiratory profile show a lower walking ability. Still, it is unknown if there is a relationship between walking ability and respiratory function that can be used to predict the latter. This cross-sectional study evaluated the relationship between walking ability and respiratory function in PwPD.MethodsSeventeen older PwPD, between 60 and 80 years old were asked to perform a 10-m walking test at self-selected, fast speed, and respiratory tests and these variables analyzed by an multiple linear regression.ResultsThe respiratory profile revealed that 44% of the patients were restrictive, 33% were obstructive, and 22% were mixed. 73% of the PwPD presented a low lung capacity, as demonstrated by the forced expiratory volume in 1 s divided by the forced vital capacity (FEV1/FVC). Multiple linear regression demonstrated that self-selected walking speed explained 53 and 58% (p = 0.027 and p = 0.016) of the variation in maximal inspiratory and expiratory pressures, respectively. The fast walking speed explained 62 and 66% (p = 0.008 and p = 0.005) of the maximal inspiratory and expiratory pressure variation, respectively. Furthermore, the locomotor rehabilitation index explained 39% (p = 0.022) of the variance in the FEV1/FVC.ConclusionThese results suggest that walking ability, particularly at self-selected and fast speeds, is a suitable screening parameter for pulmonary impairments in PwPD. Furthermore, the locomotor rehabilitation index indicates the ability to expire rapidly as a proportion of forced vital capacity in PwPD. Thus, the walking ability test can be an easily applicable and low-cost biomarker for assessing respiratory changes in PwPD.